Contested spatialities, lifestyle migration and residential tourism - Janoschka, Michael 1975-; Haas, Heiko (Abingdon, Oxon Routledge, 2014)
"Lifestyle Migration and Residential Tourism represent a major trend in individualized societies worldwide, which is attracting a rapidly growing interest from the academic community. This volume for the first time, critically analyses the spatial, social and political consequences of such leisure-oriented mobilities and migrations. The book approaches the topic from a multidisciplinary and international perspective, unifying different branches of research, such as lifestyle migration, amenity migration, retirement migration, and second home tourism. By covering a variety of regions and landscapes such as mountain and coastal areas, rural and inland communities this volume productively engages with the formal and analytical variations of the phenomenon resulting in an enriching debate at the intersection of different areas of research. Amongst others, topics like political contest and civic participation of lifestyle migrants, their impacts on local communities, social tensions and inequalities induced by the phenomenon, as well as modes of transnational living, home and belonging will be thoroughly explored. This thought provoking volume will provide deep analytical and conceptual insights into the contested geographies of lifestyle migration and further knowledge into the spatial, social and political consequences of leisure-oriented mobilities. It will be valuable reading for students, researchers and academics from a plethora of academic disciplines"--Provided by publisher.
Keywords: Emigration and immigration -- Social aspects; Retirement, Places of; Tourism; Lifestyles; Space in economics; Regional economics